Stars and stardom in Brazilian cinema - Bergfelder, Tim; Shaw, Lisa, 1966-; Vieira, João Luiz (Berghahn on film., 2017)
Despite the recent explosion of scholarly interest in "star studies," Brazilian film has received comparatively little attention. As this volume demonstrates, however, the richness of Brazilian stardom extends well beyond the ubiquitous Carmen Miranda. Among the studies assembled here are fascinating explorations of figures such as Eliane Lage (the star attraction of Sao Paulo's Vera Cruz studios), cult horror movie auteur Coffin Joe, and Lazaro Ramos, the most visible Afro-Brazilian actor today. At the same time, contributors interrogate the inner workings of the star system in Brazil, from the pioneering efforts of silent-era actresses to the recent advent of the non-professional movie star.